2013
DOI: 10.1016/b978-0-12-407706-5.00003-4
|View full text |Cite
|
Sign up to set email alerts
|

The Malaria Transition on the Arabian Peninsula: Progress toward a Malaria-Free Region between 1960–2010

Abstract: The transmission of malaria across the Arabian Peninsula is governed by the diversity of dominant vectors and extreme aridity. It is likely that where malaria transmission was historically possible it was intense and led to a high disease burden. Here, we review the speed of elimination, approaches taken, define the shrinking map of risk since 1960 and discuss the threats posed to a malaria-free Arabian Peninsula using the archive material, case data and published works. From as early as the 1940s, attempts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 33 publications
4
64
0
Order By: Relevance
“…4 Moreover, in the 1950s and 1960s, almost one-third of the Omani population had malaria. 5 Parasitological surveys conducted in the 1970s revealed that much of the northern areas of the country were mesoendemic for malaria, with the highest rates reported in the Al Batinah region where parasite rates of 13% were detected among Omani schoolchildren. 5 In 1975, a malaria control programme was initiated in Oman with financial assistance from the United Nations Development Programme; by 1979, 17 malaria units and a malaria training centre had been established.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Moreover, in the 1950s and 1960s, almost one-third of the Omani population had malaria. 5 Parasitological surveys conducted in the 1970s revealed that much of the northern areas of the country were mesoendemic for malaria, with the highest rates reported in the Al Batinah region where parasite rates of 13% were detected among Omani schoolchildren. 5 In 1975, a malaria control programme was initiated in Oman with financial assistance from the United Nations Development Programme; by 1979, 17 malaria units and a malaria training centre had been established.…”
mentioning
confidence: 99%
“…5 Parasitological surveys conducted in the 1970s revealed that much of the northern areas of the country were mesoendemic for malaria, with the highest rates reported in the Al Batinah region where parasite rates of 13% were detected among Omani schoolchildren. 5 In 1975, a malaria control programme was initiated in Oman with financial assistance from the United Nations Development Programme; by 1979, 17 malaria units and a malaria training centre had been established. 5 This first malaria control programme had several key objectives, although it was aimed principally at source reduction via the biological control of the indigenous larvivorous fish Aphanius dispar.…”
mentioning
confidence: 99%
See 3 more Smart Citations